An Analysis of the Microfinance as a Tool for Economic Growth - Vaish, Dr. P.C. (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
India is the second most populous country in the world, with a rapidly developing economy that is widening the gap between rich and poor. Microfinance allows the poor to get loans, and needs to save, invest and create a sustainable lifestyle of financial independence and growth. These loans are used productively by the poor to create their own businesses, grow their assets and address poverty all at once. Microfinance is gathering momentum to become an important force in India. Significant progress has been made over the past two decades in developing technologies to provide financial services to the poor in a sustainable way. This loan empowers the poor to start their own businesses, grow their money, and achieve long-term financial independence. Microfinance is one of the effective ways for poverty alleviation economic growth and development in emerging countries. This white paper will focus on the importance, challenges, obstacles, opportunities and outcomes of microfinance in the Indian context. Keywords: microfinance, sustainable, challenge, growth, opportunity.